2015
DOI: 10.1007/s12031-015-0551-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms of Endoplasmic Reticulum Resident IP3 Receptors

Abstract: Dysregulated calcium signaling and accumulation of aberrant proteins causing endoplasmic reticulum stress are the early sign of intra-axonal pathological events in many neurodegenerative diseases, and apoptotic signaling is initiated when the stress goes beyond the maximum threshold level of endoplasmic reticulum. The fate of the cell to undergo apoptosis is controlled by Ca2(+) signaling and dynamics at the level of the endoplasmic reticulum. Endoplasmic reticulum resident inositol 1,4,5-trisphosphate recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 151 publications
0
17
0
Order By: Relevance
“…Three predominant IP 3 R isoforms have been described (IP 3 R1, IP 3 R2 and IP 3 R3) in vertebrates with 60–80% homology in their amino acid sequences (Shah et al . ). IP 3 Rs are encoded by several genes with a number of isoforms formed through splicing (Foskett et al .…”
Section: Introductionmentioning
confidence: 97%
“…Three predominant IP 3 R isoforms have been described (IP 3 R1, IP 3 R2 and IP 3 R3) in vertebrates with 60–80% homology in their amino acid sequences (Shah et al . ). IP 3 Rs are encoded by several genes with a number of isoforms formed through splicing (Foskett et al .…”
Section: Introductionmentioning
confidence: 97%
“…Although we demonstrated that growth cone sensitivity can be controlled by intracellular signaling at the IP 3 R level, it remains unclear how this regulation occurs under physiological conditions. One possible mechanism is phosphorylation of IP 3 R subunits (reviewed in Mikoshiba, 2007;Shah et al, 2015;Vanderheyden et al, 2009). For example, cAMP-dependent protein kinase A (PKA) phosphorylates IP 3 R3 at three known sites: serines 916, 934, and 1832, in contrast to only one for each of IP 3 R1 or IP 3 R2.…”
Section: Discussionmentioning
confidence: 99%
“…ATP binds to the purinergic receptor P2YR, a GPCR, triggering production of IP 3 that binds to the IP 3 R to release Ca 2+ from the ER [64,65]. IP 3 R1 was also found to be activated by thiol modification with less than 10 µM of thimerosal, having more than this concentration actually caused an inhibitory effect [66]. Additionally, IP 3 R can be phosphorylated through protein kinase A (PKA), protein kinase B (PKB), cycline-dependent kinase 1 (CDK1), and MAP kinases [66].…”
Section: Er/sr Mediated Calcium Signalingmentioning
confidence: 99%